Marcas interacionais em Los Cachorros, de Mario Vargas Llosa - Paim, Valéria (2019)
This dissertation aims at analyzing the interaction marks in the work Los Cachorros ([1967], 2010), written by the Peruvian author Mario Vargas Llosa. This novel is about the story of the character Cuéllar, who was castrated by the bitten of a dog, called Judas, when still a child. The main point of the narrative are the problems due to the castration of the character. Regarding to the compositional aspect of the novel, the discourse of the narrative is the free indirect speech, which will be used as reference to build the methodology from the perspective of the linguistic studies. From this assumption, the methodology used has a qualitative order. This approach was related to the notions of Dino Preti (2004, 2009), of macroanalysis (contextual traits, related to genre and the characterization of the interlocutors) and microanalysis (linguistic structures that evidence clues about the turn structuring, the type of relationship between the characters and their characteristics). That implies respectively in an enunciative treatment (interactional marks), pragmatic (oral interaction marks) and morphological, syntactic and lexical (orality marks) – that is, it will be identified, described and analyzed many different compositional aspects of the free indirect speech. The theoretical referential articulates assumptions based on the Conversation Analysis, from Marcuschi (2010), Briz (2011) and Koch and Oesterreicher (2007), which ground the discussion on the relationship of the continuum between the oral and the written; of the Interactional sociolinguistics (GOFFMAN, 1988; PRETI, 2004, 2005), which deal with the specificities of the interactional orality matters; of the Spanish language, with Francisco Matte Bom (1992), Vigara Tauste (1980) e Briz (2011), which justify aspects related to the registration (oral and written); of the verbal interaction, Mikhail Bakhtin – Volochínov ([1979], 2014); and the free indirect speech, from Mikhail Bakhtin – Volochínov ([1979], 2014) and Maldonado Gonzáles (1999). This analytic proposal supported the identification of possible sense effects that the interactional marks, the oral interaction marks and the orality marks, print to a fictional text, in free indirect speech. This type of analysis of the literary text allowed to observe how the illusion of orality (PRETI, 2004) gives the narrative a singular dimension because, during the narrative, the orality traits, in general, corroborate to the characterization of the characters and to their identification from the tangle of the voices in the free indirect speech. Also, it is worth mentioning that orality marks, to a certain extent, are the element that confer fluidity to the reading, precisely because they engender traces of the characters that are revealed through the characteristics of their speech.